2020
DOI: 10.18502/ijph.v48i6.2904
|View full text |Cite
|
Sign up to set email alerts
|

Correlations among Work Stressors, Work Stress Responses, and Subjective Well-Being of Civil Servants: Empirical Evidence from China

Abstract: Background: The work stress of civil servants has gradually increased as a result of the modernization of China’s national governance system and capacity. However, research on the correlations among work stressors, work stress responses, and subjective well-being (SWB) of civil servants is scarce. Methods: In accordance with the current research status on work stress and SWB, a survey of 874 civil servants in China was carried out from May to June 2018. The revised stress response questionnaire of civil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
4
12
0
Order By: Relevance
“…Previous studies have suggested that gender, education, relationship with coworkers, physical exercise and monthly income have an effect on stress in different countries and in different people [27][28][29][30][31]. In China, male generally feel heavy stress than female ones, which conforms to the results of other surveys [32,33].…”
Section: Discussion and Limitationssupporting
confidence: 81%
See 3 more Smart Citations
“…Previous studies have suggested that gender, education, relationship with coworkers, physical exercise and monthly income have an effect on stress in different countries and in different people [27][28][29][30][31]. In China, male generally feel heavy stress than female ones, which conforms to the results of other surveys [32,33].…”
Section: Discussion and Limitationssupporting
confidence: 81%
“…The goal of building a moderately prosperous society in all respects in China, with the implementation of the accountability system and the reform of rank promotion, led to more rigorous assessment standards and the rare chance of promotion in civil servants [1]. In this case, civil servants constantly faced the pressure of occupation, individual and society [2]. Studies have shown that the special work pressure of civil servants is related to the mental health such as depression and anxiety of civil servants [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sackey and Sanda [12] identified the work-related stressors as the key predictors of women managers' ill-health in the work environment using the Depression, Anxiety and Stress Scale, the Beck's Anxiety Inventory, and the Occupational Stress Indicator. Zhang et al [13] identified the work stressors of civil servants by the revised work stress questionnaires, which stressors were sorted by interpersonal relationship, work particularity, career prospect, work task, perfectionism, and job responsibility. Barbaranelli et al [14] identified the risks associated with work stress by the revised selfadministered questionnaire.…”
Section: Introductionmentioning
confidence: 99%